Curso de capacitação “caminhos d’agente”: formação em envelhecimento para agentes comunitários de saúde do município de Sobral-Ce - Andrade, Maria de Jesus Bastos Gomes (2023)
Increasing and accelerated aging has become one of the greatest challenges for Public Health Policies aimed at the elderly. According to the Brazilian Institute of Geography and Statistics IBGE, according to it s latest census of 2022, in Brazil the population of elderly people h as alread y exceeded 31 million. This scenario indicates that hea lth professionals, especially in Primary Care, need to be prepared to deal with this demand. The National Policy for the Elderly PNSPI, from 2006, defined the gatewa y to assistance for the elderly as Primary Care and Continuing Education is identified as one of the paths for this preparation. This qualitative and interventional research arises within this context from the Professional Master's Degree in Psychology and Public Policies in partn ership wi th the Municipality of Sobral. Its purpose was to offer a training course on aging for CHAs in the municipality of Sobral CE based on the Problemati zing Methodology with the Maguerez Arch. The sample was for convenience an d consisted of 31 CHAs, representatives of 20 different territories in Sobral. The course was called “Caminhos D’Agente”, it had the character of an extension course with 40h/a certification by UFC. It included t wo main thematic axes: Mental Health and Health Care for the Elderly, however this study will include the description and analysis of the second axis. The course activities took place in eight meetings, spread over a month. Ba sed on what each phase of the Maguerez Arc proposes, the ACS observed thei r reality of dealing with the elderly and realized that the concepts of old, old age and aging are still rooted in prejudice. Regarding the profile of the elderly people served, they reinforced the importance of understanding the plurality and diversity of the elderly and their ol d ages. T hey raised family issues and the lack of support from t he team and/or other services as challenges. More than 70% of the CHA responded that learning with this methodology was very effective and the importance of Continuing Education for improving their practices and that of the entire healthcare team. It is hoped that through this research other studies will be carried out and the theme of aging can become something more recurrent in the training offered to CHAs.